Complex prophylaxis of postoperative complications in colorectal surgery - B. М. Datsenko; Т. I. Таmm; А. B. Datsenko; А. V. Кirillov; V. V. Sedak; S. N. Posokhov (Клінічна хірургія)
Objective. To improve the immediate results of surgical treatment of colorectal cancer, using more effective prophylaxis of morbidity.